(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Large cystic mass is an unusual presentation of papillary thyroid carcinoma, accounting for less than 10% of cases. To make a diagnosis of papillary thyroid carcinoma is challenging since the tumour can mimic a benign lateral neck mass. Therefore, a systematical approach to a patient with neck lump is required so that accurate diagnosis and appropriate treatment can be made. We present a case of a 25-year-old female presenting with an asymptomatic left neck cystic mass diagnosed as a metastatic lymph node of papillary thyroid carcinoma only after surgery. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 92-95